MODERN TRENDS IN JEWELRY DESIGN IN CHINA - Gao, Anqi; Pashkevych, Kalyna Livianivna (Theory and practice of design, 2025)
The Purpose of the article is to examine key trends in contemporary Chinese jewelry design across Mainland China, Hong Kong, and Taiwan. It explores how designers balance tradition and innovation, develop diverse typologies, adopt new materials and technologies, and embed cultural meaning into their works. The goal is to understand how these practices shape a distinctive global identity rooted in Chinese heritage. Methodology. Adopting a qualitative approach, this research combines literature review, visual content analysis, case studies, and regional comparison. It analyzes representative works by Chinese designers, focusing on materials, themes, techniques, and symbolic expression. Results. The findings show that contemporary Chinese jewelry design is characterized by multi-dimensional creativity expressed through narrative-driven themes, hybrid aesthetic languages, and typological expansion. Designers merge classical Chinese symbols, such as dragons, gourds, ruyi locks, and lotus flowers, with contemporary minimalism and global design vocabularies. Technical innovations, including the use of titanium, 3D printing, and new gemstone-setting techniques, have redefined the structural possibilities of jewelry. Symbolism plays a central role in design expression, and many works embed emotional, philosophical, or mythological content rooted in Chinese traditions. Moreover, designers across regions demonstrate strong cross-disciplinary tendencies, often blurring boundaries between jewelry, sculpture, fashion, and body art. While Hong Kong designers emphasize refinement and East- West luxury fusion, and Taiwanese designers show poetic sensitivity and artisanal craft, Mainland Chinese designers lead in experimental expressions and assertive cultural representation. Despite regional distinctions, a converging design ethos has emerged, forming a recognizable Contemporary Chinese Jewelry Design identity. Scientific novelty. This article presents an in-depth, cross-regional synthesis of Chinese jewelry design. It integrates conceptual, material, and aesthetic perspectives into a coherent analytical framework, contributing to global design scholarship. Practical relevance. The findings offer guidance for designers, curators, and educators seeking to engage with Chinese jewelry design. The study emphasizes the role of heritage, sustainability, and cross-media practices in shaping creative outcomes. It identifies actionable trends such as new traditionalism and digital craft as future directions for both design education and industry innovation.